The risk of ovarian cancer in hormone replacement therapy users: a systematic review and meta-analysis - Xiang, Hongqin; Wang, Liangying; Sun, Liping; Xu, Song (Frontiers in Endocrinology, 2024)
Background With the increasing use of hormone replacement therapy (HRT), there is a need to understand its impact on the occurrence of female malignant tumors. This systematic review and meta-analysis aimed to assess the risk of ovarian cancer associated with HRT and its related risk factors. Methods PUBMED, OVID, Embase, Cochrane, and Web of Science were searched from 1980 to April 2022 to identify studies on the risk of ovarian cancer and hormone replacement therapy. The random-effects model was used to estimate the pooled risk of HRT in ovarian cancer, both in cohort studies and case-control studies. Additionally, the analysis examined the outcomes associated with different types of estrogen plus progesterone regimens. Meta-regression and sensitive analysis were performed to evaluate the heterogeneity. Results 21 cohort studies (involving 15,313 cases and 4,564,785 participants) and 30 case-control studies (including 18,738 cases and 57,747 controls) were analyzed. The pooled risks of ovarian cancer for HRT users were 1.20 (95% confidence interval [CI] 1.01–1.44) from cohort studies and 1.13 (95%CI 1.04–1.22) from case-control studies. However, after restricting the study period to recent decades, the significant results indicating a higher risk disappeared in cohort studies conducted after 2010 and in case-control studies conducted after 2006. Furthermore, the continuous use of estrogen-progesterone replacement therapy (EPRT) was associated with a risk comparable to that of sequential use. Subgroup analysis showed that both estrogen replacement treatment (ERT) and EPRT had minor risks; The risk further increased with prolonged exposure time, particularly for durations exceeding 10 years. Additionally, serous ovarian cancer appeared to be more susceptible than other pathological types. Conclusion The risk of ovarian cancer associated with HRT has been decreasing over time. However, ERT may increase this risk, particularly when used for an extended period. It is recommended that long-time users consider continuous EPRT as a safer alternative. Systematic review registration www.crd.york.ac.uk/prospero/, identifier CRD42022321279.